A Multi-Purpose Approach to the Mechanisms of Action of Two Biocides (Benzalkonium Chloride and Dibromonitrilopropionamide): Discussion of Pseudomonas fluorescens’ Viability and Death - Barros, Ana C.; Melo, Luis F.; Pereira, Ana (Frontiers in Microbiology, 2022)
Biocides are widely used in water treatment for microbiological control. The rise of antimicrobial resistance and the need to assure properly managed water systems require a better understanding of the mechanisms of action of biocides and of their impact on cell’s viability as a function of dosage concentrations. The present work addresses these two aspects regarding the biocides BAC (benzalkonium chloride) and DBNPA (dibromonitrilopropionamide) - two biocides commonly found in the water treatment industry. For that, the following parameters were studied: culturability, membrane integrity, metabolic activity, cellular energy and the structure and morphology of cells. Also, to assess cell’s death, a reliable negative control, consisting of cells killed by autoclave (dead cells), was introduced. The results confirmed that BAC is a lytic biocide and DBNPA a moderate electrophilic one. Furthermore, the comparison between cells exposed to the biocides’ minimum bactericidal concentrations (MBCs) and autoclaved cells revealed that other viability parameters should be taken into consideration as ‘death indicators’. The present work also shows that only for the concentrations above the MBC the viability indicators reached values statistically similar to the ones observed for the autoclaved cells (considered to be definitively dead). Finally, the importance of considering the biocide mechanism of action in the definition of the viability parameter to use in the VBNC (viable but non culturable) determination is discussed.